Unusual cause of acute abdomen – omental infarction occurring in a child with cyclical neutropenia - Ventham, Nicholas (Ann R Coll Surg Engl, 2010)
Omental infarction is a rare cause of acute abdomen in childhood. We describe a case of omental infarction mimicking acute appendicitis occurring in a child with cyclical neutropenia. Neutropenic enterocolitis, a serious cause of the acute abdomen, has been linked with cyclical neutropenia. In neutropenic patients, omental infarction when diagnosed pre-operatively can be managed conservatively with the focus on improving the neutrophil count. If after imaging the diagnosis is in doubt, there should be a low threshold for laparoscopy. The low incidence of omental infarction will continue to mean that it is a diagnosis made at operation for suspected appendicitis. In these cases, the infarcted tissue may be removed by the laparoscopic or open technique.